2017
DOI: 10.11648/j.jgo.20170506.11
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review: Contraceptive Knowledge and Use in Saudi Arabia

Abstract: Introduction: Contraceptive use was remaining as paramount importance to women's health. In the kingdom of Saudi Arabia (KSA), it was found that up to 62.8% of fertile married Saudi women do not use contraceptive methods. While, the women who are using contraceptive methods, they do not have adequate knowledge. The purpose of the systematic review in the current study is to retrieve all researches that related to contraceptive method in KSA. Methods: two questions were used to guide the review were: (1) What a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 11 publications
1
14
1
Order By: Relevance
“…[ 25 26 ] A recent review explained this major source is due to Saudi cultural norms and lack of school curriculum to educate women about contraceptives and reproductive health. [ 23 ] In contrast a previous study from Aseer region reported that the media, like television, internet, and newspapers, played a major role in raising awareness (40.8%). [ 14 ] This difference could be explained by the difference in their sample socio-demographic characteristics.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…[ 25 26 ] A recent review explained this major source is due to Saudi cultural norms and lack of school curriculum to educate women about contraceptives and reproductive health. [ 23 ] In contrast a previous study from Aseer region reported that the media, like television, internet, and newspapers, played a major role in raising awareness (40.8%). [ 14 ] This difference could be explained by the difference in their sample socio-demographic characteristics.…”
Section: Discussionmentioning
confidence: 87%
“…[ 15 ] Furthermore, a review documented that the most popularly known contraceptives in the Gulf area are oral contraceptive pill and IUD. [ 23 ] Regarding family planning methods complications, 41.2% of the participants knew about mood fluctuations followed with clots formation (24.0%), weight gain (21.2%), bleeding (20.8%), while pain and depression were the least identified complications, which is consistent with a study from Qaseem, KSA[ 24 ] that documented that the most common complications identified by women were headache (27.12%), emotional change (27.12%), depression (16.5%), and nausea (11.33%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, Two-fifths (40%) of the study subjects who were implants users had high perceived severity to problems associated with its utilization compared to approximately an equal percent (25.21% &27.50%) of those who were either IUDs or OCPs users, respectively. (8) illustrates that there was a statistically significant positive correlation between study subject's perceived benefits and their contraceptive methods utilization (MCP = 0.00). Almost all (94.96% & 92%) of the subjects who were either IUDs or implants users had high perceived benefits to their contraception uptake compared to three-fourths (75% &71.83 %) of those who were either OCPs or injectables users, respectively.…”
Section: Resultsmentioning
confidence: 93%
“…• Moderate (6)(7)(8) • High (9-12) Secondly, perceived severity: It included (7items) from 7-28 and it ranked as follow:…”
Section: Tools Of Data Collection: Two Tools Were Used For Data Collementioning
confidence: 99%